2018
DOI: 10.1038/s41419-017-0128-y
|View full text |Cite
|
Sign up to set email alerts
|

Transmembrane protein 170B is a novel breast tumorigenesis suppressor gene that inhibits the Wnt/β-catenin pathway

Abstract: The identification of specific drug targets guides the development of precise cancer treatments. Compared with oncogenes, tumor suppressor genes have been poorly studied in the treatment of breast cancer. We integrate the microRNA expression array from GEO (Gene Expression Omnibus) and TCGA (The Cancer Genome Atlas) databases in clinical breast cancer tissues, and find that miR-27a is significantly upregulated and correlated with poor survival outcome and tumor progression. Transmembrane protein 170B (TMEM170B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 39 publications
0
27
0
Order By: Relevance
“…To our knowledge, the key switch in the canonical Wnt pathway is the protein β-catenin, upon Wnt pathway activation in the presence of Wnt ligands, the phosphorylated LRP receptor might act to directly inhibit GSK-3β and thereby promote β-catenin stabilization and nuclear accumulation 26 . Therefore, β-catenin forms an active complex with LEF (lymphoid enhancer factor) and TCF (T-cell factor) proteins 27 and activates transcription of downstream target genes including c-myc, cyclin D1, vimentin, c-jun 28 , which are the basis for tumorigenesis. Strikingly, AC104041.1 knockdown resulted in marked reduction in Wnt2B, nuclear translocation of β-catenin, c-myc, and vimentin expression, which were diminished by miR-6817-3p inhibitors (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To our knowledge, the key switch in the canonical Wnt pathway is the protein β-catenin, upon Wnt pathway activation in the presence of Wnt ligands, the phosphorylated LRP receptor might act to directly inhibit GSK-3β and thereby promote β-catenin stabilization and nuclear accumulation 26 . Therefore, β-catenin forms an active complex with LEF (lymphoid enhancer factor) and TCF (T-cell factor) proteins 27 and activates transcription of downstream target genes including c-myc, cyclin D1, vimentin, c-jun 28 , which are the basis for tumorigenesis. Strikingly, AC104041.1 knockdown resulted in marked reduction in Wnt2B, nuclear translocation of β-catenin, c-myc, and vimentin expression, which were diminished by miR-6817-3p inhibitors (Fig.…”
Section: Resultsmentioning
confidence: 99%
“… 163 With many of Wnt ligands being able to promote the progression of breast tumors, the restoration of many Wnt inhibitors that has been silenced by mechanisms such as DNA methylation and miRNAs in tumors has effectively attenuated tumor growth. 164 , 165 , 166 Wnt pathway activation was shown to increase radiation resistance of progenitor cells in the mouse mammary gland and human breast cancer cell lines, 167 , 168 indicating that Wnt signaling is involved in resistance to current anticancer drugs potentially by regulating stem and progenitor cell populations.…”
Section: Major Signaling Pathways In Breast Cancer Development and Prmentioning
confidence: 99%
“…Moreover, Li et al also reported that miR-27a could function as a suppressor in breast cancer. It targeted and down-regulated TMEM170B inhibiting the Wnt/β-catenin pathway, which could suppress breast cancer proliferation, migration, and tumorigenesis 18. Apart from the studies above which suggesting miR-27a could play a vital role in repressing many tumors growth, there were evidences illustrating that it also acted as an enhancer in the angiogenesis of tumors.…”
Section: Mir-27a Influences Tumor Biologymentioning
confidence: 99%